2012
DOI: 10.1158/1055-9965.epi-12-0229
|View full text |Cite|
|
Sign up to set email alerts
|

A Nonsynonymous Polymorphism inIRS1Modifies Risk of Developing Breast and Ovarian Cancers inBRCA1and Ovarian Cancer inBRCA2Mutation Carriers

Abstract: Background We previously reported significant associations between genetic variants in insulin receptor substrate 1 (IRS1) and breast cancer risk in women carrying BRCA1 mutations. The objectives of this study were to investigate whether the IRS1 variants modified ovarian cancer risk and were associated with breast cancer risk in a larger cohort of BRCA1 and BRCA2 mutation carriers. Methods IRS1 rs1801123, rs1330645, and rs1801278 were genotyped in samples from 36 centers in the Consortium of Investigators o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Low‐risk variants, largely identified by genome‐wide association studies, are usually common and cause subtle functional effects, such as small but significant changes in gene expression due to altered activity of proximal and distal regulatory elements (reviewed in Bogdanova, Helbig, & Dork, ; Ghoussaini, Pharoah, & Easton, ; Skol, Sasaki, & Onel, ). Evidence suggests that combinations of low, moderate, and high‐risk variants could confer a clinically significant risk of disease (Ding et al., ; Kuchenbaecker et al., ; Sawyer et al., ). Identification and evaluation of all such variants is therefore crucial for accurately predicting BC risk.…”
Section: Introductionmentioning
confidence: 99%
“…Low‐risk variants, largely identified by genome‐wide association studies, are usually common and cause subtle functional effects, such as small but significant changes in gene expression due to altered activity of proximal and distal regulatory elements (reviewed in Bogdanova, Helbig, & Dork, ; Ghoussaini, Pharoah, & Easton, ; Skol, Sasaki, & Onel, ). Evidence suggests that combinations of low, moderate, and high‐risk variants could confer a clinically significant risk of disease (Ding et al., ; Kuchenbaecker et al., ; Sawyer et al., ). Identification and evaluation of all such variants is therefore crucial for accurately predicting BC risk.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo overexpression of IRS-1 and IRS-2 in the mammary gland of murine models was found to cause mammary tumorigenesis and metastasis (35), suggesting that IRS-1 and IRS-2 behave as oncogenes in vivo . The Gly972Arg IRS-1 polymorphism has been associated with increased BC risk for BRCA1 class II mutation carriers (10). In the present study, mutational analysis of IRS in BC and CRC identified several variants with pathogenic potential.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, IRS-1 G972R significantly modifies the risk of developing ovarian cancer in BRCA1 and BRCA2 mutation carriers (10). Our previous results suggest that IRS-1 may influence adenoma formation, CRC progression and liver metastasis (11).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this, studies of the relatives of populationbased or hospital-based cases selected regardless of a family history have found lower estimates of penetrance to age 70 years, less than 60 % for breast cancer risk for BRCA1 mutation carriers and 30-56 % for BRCA2 mutation carriers [6,[8][9][10][11][12]. In addition, some studies have found evidence that risk varies by specific mutations [13,14], other genetic modifiers [15][16][17], birth cohort [18,19], and reproductive and lifestyle factors [20,21].…”
Section: Introductionmentioning
confidence: 90%